Synthesis of Wound-Healing Keratin Hydrogels Using Chicken Feathers Proteins and Its Properties - Priyaah, Kumaran; Gupta, Arun; Sharma, Swati (Innovare Academic Sciences, 2017)
Objective: A novel cross-linked keratin hydrogel was prepared by integrating keratin from chicken feather into an aloe-vera, Chitosan and honey based dressing formulation separately. Methods: Keratin fibres extracted from chicken feathers are eco-friendly, non-abrasive, biodegradable, insoluble in organic solvents and having good mechanical properties, hydrophobic behaviour, low density and finally cheap. Keratin based hydrogels were prepared with five types of ingredients and studied for their wound healing properties. The analysis of keratin-based hydrogel was done by Fourier Transform Infra-red Spectroscopy (FTIR) and X-ray diffraction (XRD) analysis. Results: Keratinocytes containing keratin travel from the wound border to initiate the process of healing. The characteristics of keratin-based hydrogel derived from chicken feather made it an effective wound care therapeutic product. X-ray diffraction (XRD) analysis showed the crystallinity index in between 30-50% of the hydrogen. Conclusion: The test for swelling and solubility were carried out on the hydrogen to determine the solid content and water absorbance capacity. Overall, this product is safe to use as an effective wound healing product with appropriate properties.